Relación entre el perdón, la reconciliación y la salud mental de las víctimas de la violencia socio-política = Relationships among forgiveness, reconciliation and mental health in victims by socio-political violence - López-López, Wilson 19XX- (Revista de victimología, 2016)
Victims of socio-political violence must not only face dispossession and material damages, but also health effects. Only in Colombia, there are 7.675.032 victims who have experienced forced disappearance, sexual violence, forced recruitment, anti-personnel mines, massacres, murders, and kidnappings. These events have led to emotional, psychological, moral, political, and cultural damages. Forgiveness and reconciliation are some of the strategies we deem fundamental in order to intervene on, and contribute to, psychological well-being, and in fact a positive effect of them for both victims and offenders has already been documented. Thus, the goal of this paper was to conduct a review of the main publications in Scopus,Web of Knowledge, APA PsycArticles and SciELO, dealing with seeking of forgiveness, health, anxiety, Post-Traumatic Stress Disorder and victims. From the resulting papers, we selected only those relating forgiveness and socio-political violence. Reports from Colombian institutions and newspaper clips were also considered. In the reviewed publications, three topic groups were identified: implications of violent events on mental health; forgiveness and reconciliation as strategies to improve the psychological well-being of victims; and finally, programs or strategies of intervention on the victims’ psychological suffering, with forgiveness and reconciliation as strategies. The main conclusions are that forgiveness is a strategy that can be learned and that can mobilize emotional and social processes toward well-being; that more attention to a gender perspective is needed in psychosocial interventions; that more detailed knowledge of how reconciliation processes work and are managed; and that Social Sciences need to base their interventions on scientific knowledge, sharing perspectives such as that of transformative justice.